Exploring epistemic cognition in different task contexts - Köksal, Alp. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
In this study epistemic performance in different task contexts was studied. There were, 2 physics professors, 4 teaching physics undergraduate students and 4 social sciences undergraduate students. Apt-AIR framework was adopted as the analytical framework. Data were collected using think aloud protocol and semi-structured interviews. In data analysis, (a) various examples for cognitive elements of epistemic performance were identified, (b) various behaviours related to metacognitive elements of epistemic performance were encountered and (c) comparisons were made between groups’ epistemic performances. The first task context was related with physics. Physicists have demonstrated a wide range of cognitive and metacognitive elements of epistemic performance. By doing so they have helped us to paint a picture of disciplinary characteristics of physics. All groups have identified experimentation and observations as reliable processes for producing or evaluating a knowledge claim. The theme of the second task context was mandatory covid vaccine. While evaluating knowledge claims and choosing sides, physicists have looked for the data. They have argued there were adequate amount of data during the time the video was shot. Teaching physics students, mostly trusted to their personal experiences and emotions. The frequency of demonstrated metacognitive elements of epistemic performance was lowest among teaching physics students compared to other two groups. The third group, social sciences students have kept well-being of the society at front while engaging with the second issue. The findings of the study tells us epistemic performance is contextual and Apt-AIR framework works as an analytical framework while capturing the cognitive and metacognitive elements of epistemic performance. The results suggest, there is a need to develop pre service teachers’ ability to perform apt epistemic performance.
Keywords: Cognitive learning.; Metacognition.